Repeated Glucose Deprivation/Reperfusion Induced PC-12 Cell Death through the Involvement of FOXO Transcription Factor - Han, Na (Diabetes Metab J, 2016)
BACKGROUND: Cognitive impairment and brain damage in diabetes is suggested to be associated with hypoglycemia. The mechanisms of hypoglycemia-induced neural death and apoptosis are not clear and reperfusion injury may be involved. Recent studies show that glucose deprivation/reperfusion induced more neuronal cell death than glucose deprivation itself. The forkhead box O (FOXO) transcription factors are implicated in the regulation of cell apoptosis and survival, but their role in neuronal cells remains unclear. We examined the role of FOXO transcription factors and the involvement of the phosphatidylinositol 3-kinase (PI3K)/Akt and apoptosis-related signaling pathways in PC-12 cells exposed to repeated glucose deprivation/reperfusion. METHODS: PC-12 cells were exposed to control (Dulbecco's Modified Eagle Medium [DMEM] containing 25 mM glucose) or glucose deprivation/reperfusion (DMEM with 0 mM glucose for 6 hours and then DMEM with 25 mM glucose for 18 hours) for 5 days. MTT assay and Western blot analysis were performed for cell viability, apoptosis, and the expression of survival signaling pathways. FOXO3/4',6-diamidino-2-phenylindole staining was done to ascertain the involvement of FOXO transcription factors in glucose deprivation/reperfusion conditions. RESULTS: Compared to PC-12 cells not exposed to hypoglycemia, cells exposed to glucose deprivation/reperfusion showed a reduction of cell viability, decreased expression of phosphorylated Akt and Bcl-2, and an increase of cleaved caspase-3 expression. Of note, FOXO3 protein was localized in the nuclei of glucose deprivation/reperfusion cells but not in the control cells. CONCLUSION: Repeated glucose deprivation/reperfusion caused the neuronal cell death. Activated FOXO3 via the PI3K/Akt pathway in repeated glucose deprivation/reperfusion was involved in genes related to apoptosis.